CORPORATE ROLE IN INCREASING RICE FARMERS INCOME - Darwis, Valeriana; Muslim, Chairul (Politeknik Negeri Lampung, 2023)
Farmers' income can be increased by optimizing production and increasing product added value. To achieve this, the Ministry of Agriculture establishes agricultural corporation activities. One of those participating in agricultural corporate activities is Tani Mulus Gapoktan in Indramayu Regency. This paper aims to find out the implementation of corporate activities and how much the increase in income received by members. To find out the implementation of activities using descriptive analysis and how much the increase in income of members using partial budget analysis. The research was conducted in early 2021 with the results of research on the implementation of agricultural corporations, including: (i) establishing an institution requires a process and time, (ii) Tani Mulus Corporation has succeeded in building a network of rice products from upstream to downstream, (iii) maintaining relationships in the form of agreements on each network. Members who participate in corporate activities experience an increase in their income per hectare by IDR. 4,985,000. The role of corporations can be further enhanced by: (i) optimizing the use of paddy fields in the corporate area, (ii) increasing grain processing by increasing the number of members who borrow from corporations and (iii) increasing corporate income by purchasing Rice Milling Unit.